General Comment No. 3 on the African Charter on Human and Peoples' Rights: The Right to Life (Article 4) Adopted during the 57th Ordinary Session of the African Commission on Human and Peoples' Rights held from 4 to 18 November 2015 in Banjul, The Gambia (Pretoria University Law Press (PULP), 2016)
The jurisprudence of the African Commission on Human and Peoples' Rights has widely recognised the right to life as a foundational right. Without the right to life, other rights cannot be implemented. The Commission adopted General Comment No.3 on the African Charter on Human and Peoples' Rights on the right to life (Article 4) during its 57th Ordinary Session, held in Banjul, The Gambia, in November 2015. It is designed to guide the interpretation and application of the right to life under the Charter and to ensure its coherent application to a range of situations, including its implementation at the domestic level. The General Comment does not put in place new standards or highlight best practices but rather sets out the Commission's perspective on dimensions of this universally recognised right. The text is also available, in the four official languages of the African Union, on the African Commission's website: www.achpr.org